2018
DOI: 10.1097/corr.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Does Tourniquet Use in TKA Increase Postoperative Pain? A Systematic Review and Meta-analysis

Abstract: Background Although tourniquets are commonly used during TKA, that practice has long been surrounded by controversy. Quantifying the case for or against tourniquet use in TKA, in terms of patient-reported outcomes such as postoperative pain, is a priority. Questions/purposes The purpose of this study was to meta-analyze the available randomized trials on tourniquet use during TKA to determine whether use of a tourniquet during TKA (either for the entire procedure or some portion of it) is associated with (1) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 46 publications
5
42
0
Order By: Relevance
“…Previous studies on the timing of releasing tourniquets showed that releasing the tourniquet before the wound recovery would cause an increase in total blood loss but decrease the risk of complications 31,32 . In contrast, in a meta‐analysis, the authors found that the mean pain scores of patients treated with tourniquets were significantly higher than those treated without tourniquets, with the mean pain scores of 5.23 ± 1.94 cm and 3.78 ± 1.61 cm, respectively 33 . Similar with this meta‐analysis, our results showed that the higher VAS on the second day after TKA related to the tourniquet duration, the drain tube extubation time, and drain tube diversion ( P = 0.002, P = 0.025 and P = 0.027), which indicated that the tourniquet should be release as early as possible to relieve pain.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies on the timing of releasing tourniquets showed that releasing the tourniquet before the wound recovery would cause an increase in total blood loss but decrease the risk of complications 31,32 . In contrast, in a meta‐analysis, the authors found that the mean pain scores of patients treated with tourniquets were significantly higher than those treated without tourniquets, with the mean pain scores of 5.23 ± 1.94 cm and 3.78 ± 1.61 cm, respectively 33 . Similar with this meta‐analysis, our results showed that the higher VAS on the second day after TKA related to the tourniquet duration, the drain tube extubation time, and drain tube diversion ( P = 0.002, P = 0.025 and P = 0.027), which indicated that the tourniquet should be release as early as possible to relieve pain.…”
Section: Discussionmentioning
confidence: 90%
“…While the current study provides compelling evidence that tourniquet use does not compromise muscle or knee function after TKA [1], the patient population that may be at risk for tourniquet-related complications has not been clearly established nor has the potential benefit of tourniquet use on long-term cemented implant fixation. Future studies should assess the relative risk of tourniquet related adverse effects in presumed high-and low-risk patient populations.…”
Section: Where Do We Need To Go?mentioning
confidence: 90%
“…The studies included in the metaanalysis by Deering and colleagues [1] report postoperative pain, ROM, and hospital length of stay. But if tourniquet use improves cement fixation, then long-term studies are needed to determine whether tourniquets have any effect on the durability of cemented implant fixation in TKA.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 1 more Smart Citation
“… Anti-tourniquet Schnettler et al [ 8 ] – Tourniquet use with tranexamic acid leads to more blood loss than tranexamic acid alone. Functional outcomes Pro-tourniquet Goel et al (randomized controlled study) [ 9 ] – Tourniquet use has similar in-hospital functional results compared to no tourniquet McCarthy et al [ 20 ] – No clinically important differences in pain, ROM, and LOS during an in-hospital stay between groups. Anti-tourniquet Huang et al (randomized controlled study) [ 21 ] – No tourniquet and tranexamic acid leads to less pain, less swelling, better ROM, and satisfaction during hospital stay compared to tourniquet use Chen et al (randomized controlled study) [ 22 ] – Half-course tourniquet use leads to less pain and better ROM than full-course tourniquet use.…”
Section: Discussionmentioning
confidence: 99%